2012
DOI: 10.3198/jpr2011.07.0385crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Kharoba’: A Bread Wheat Cultivar Developed through Doubled Haploid Breeding

Abstract: ‘Kharoba’ (Reg. No. CV‐1068, PI 664028), a hard red spring wheat (Triticum aestivum L.) cultivar developed using doubled haploid technology by the Institut National de la Recherche Agronomique (INRA), Morocco, and tested as 00DHBW300, was approved for release in 2010 by the Office National de Sécurité Sanitaire des Produits Alimentaires (ONSSA), Morocco. Kharoba was selected from the doubled haploids derived from the cross ‘Altar 84’/Aegilops squarrosa 221//‘Pastor’/3/k134(6)/‘Veery’//‘Bobwhite’/‘Pavon’/4/‘Til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Therefore, these traits have good potential in order to select and to conserve genotypes. So that, information of genetic diversity, evaluation of the genetic relationships among these genotypes can provide relevant guidelines in selecting parents and for designing new breeding strategies for wheat cultivar improvement especially for drought tolerance (Elhaddoury et al, 2012). The findings of present study are also in agreement with (Sinha et al, 2006;Kamboj, 2007;Baloch et al, 2013) reported highly significant differences for among all the traits.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, these traits have good potential in order to select and to conserve genotypes. So that, information of genetic diversity, evaluation of the genetic relationships among these genotypes can provide relevant guidelines in selecting parents and for designing new breeding strategies for wheat cultivar improvement especially for drought tolerance (Elhaddoury et al, 2012). The findings of present study are also in agreement with (Sinha et al, 2006;Kamboj, 2007;Baloch et al, 2013) reported highly significant differences for among all the traits.…”
Section: Resultssupporting
confidence: 91%
“…The Moroccan wheat cultivars used in this study represent the most advanced breeding lines released for cultivation in Morocco and encompass important gene pools adapted to Morocco and the North Africa region. Therefore, information of genetic diversity, identification of specific alleles, genes or loci and assessment of the genetic relationships among these cultivars can provide relevant guidelines in selecting parents and for designing new breeding strategies for wheat cultivar improvement, especially, against leaf rust, yellow rust and Hessian fly, which are considered as most destructive biotic stresses in Morocco (Elhaddoury et al 2012 ). Lombardi et al ( 2014 ) reported that selection of divergent parental genotypes for breeding should be made actively on the basis of systematic assessment of genetic distance between genotypes, rather than passively based on geographical distance.…”
Section: Discussionmentioning
confidence: 99%
“…In each row, seeds were sown by hand at a 2 cm depth maintaining a 10 cm space between plants, and the total plot size maintained was 0.6 m 2 . In general, the Tessaout research station represents a typical Mediterranean semi-arid environment, characterized by a hot dry summer with an annual rainfall of 266 mm [48]. The Marchouch station also represents a Mediterranean semi-arid environment, but with higher annual precipitation (400 mm) [49].…”
Section: Plant Materials and Study Areamentioning
confidence: 99%